Ontology-Based Resource Modeling and Matching Framework in Avionics Systems. (12th September 2022) - Du, Xiaoyan; Du, Chenglie; Chen, Jinchao; Dong, Chunhui; Liu, Yifan
Abstract : In order to realize rapid service-oriented construction of resources and efficient supply-demand matching in avionics systems, an ontology-based resource modeling and matching framework in avionics systems is proposed. First, this paper constructs a hierarchical resource organization framework based on virtual resource pool, covering dispersed and heterogeneous avionics resources and shielding the differences and diversity of resources; next, introduces ontology technology into resource modeling and encapsulates resources as services using the idea of "resource as a service, " facilitating the access and control of resources; in addition, proposes a matching framework which takes into account the energy consumption, in which it firstly tries to find a list of resources which can meet task requirements by a stepwise intelligent matching strategy based on semantic similarity, and the resources in the list will then be sorted according to the energy consumption. Finally, a radar detection case is taken to demonstrate that the proposed model and method are feasible and effective.